1997
DOI: 10.1001/jama.1997.03540390035032
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence of Generic and Brand-name Levothyroxine Products in the Treatment of Hypothyroidism

Abstract: The 4 generic and brand-name levothyroxine preparations studied are different but are bioequivalent by current Food and Drug Administration criteria and are interchangeable in the majority of patients receiving thyroxine replacement therapy. Further investigation is required to determine whether our results are equally applicable to all existing levothyroxine preparations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(28 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…Diese Resorptionsstudien wurden zwar vielfach angegriffen, da sie meist mit gesunden Kontrollpersonen durchgeführt worden sind. Dennoch gibt es eindeutige Unterschiede in der Bioverfügbarkeit einzelner Präparate, die zwischen 0,8 und 1,25 schwanken kann und damit klinisch relevant ist [9]. Man kann somit nicht ohne Kontrolle der Schilddrüsenfunktion Levothyroxinpräparate verschiedener Hersteller austauschen.…”
Section: Substitution Von Schilddrüsenhormonenunclassified
“…Diese Resorptionsstudien wurden zwar vielfach angegriffen, da sie meist mit gesunden Kontrollpersonen durchgeführt worden sind. Dennoch gibt es eindeutige Unterschiede in der Bioverfügbarkeit einzelner Präparate, die zwischen 0,8 und 1,25 schwanken kann und damit klinisch relevant ist [9]. Man kann somit nicht ohne Kontrolle der Schilddrüsenfunktion Levothyroxinpräparate verschiedener Hersteller austauschen.…”
Section: Substitution Von Schilddrüsenhormonenunclassified
“…22 The President of Knoll wrote to the journal editor to say that the company had decided to allow publication "first because we gained a better understanding of the importance of supporting academic freedom and the peer review process; and second, we were concerned that intense media speculation about the study's findings and conclusions was being regarded as fact. Clearly the manuscript needed to be published so the study and our concerns about it could be evaluated in the proper context."…”
Section: Other Examplesmentioning
confidence: 99%
“…For example, a manuscript reporting on a trial comparing the bioequivalence of generic and brand levothyroxine products, which had failed to produce the results desired by the sponsor of the study, Boots Pharmaceuticals, was withdrawn because Boots took legal action against the university and the investigators. The actions of Boots, recounted in detail by one of the editors of JAMA, Drummond Rennie, 74 meant that publication of the paper 75 was delayed by about seven years. In a national survey of life-science faculty members in the United States, 20% of faculty members reported that they had experienced delays of more than six months in publication of their work and reasons for not publishing included "to delay the dissemination of undesired results".…”
Section: The Influence Of External Funding and Commercial Interestsmentioning
confidence: 99%